Tobacco smoking and smokeless tobacco use among people living with HIV in Zambia: Findings from a 2023 National NCD/HIV Survey. - Cosmas Zyambo; Paul Somwe; Chomba Mandyata; Mwiche Musukuma; Phoebe Bwembya; Henry Phiri; Malizgani P Chavula; Hikabasa Halwindi; Joseph Zulu; Wilbroad Mutale (PLoS ONE)
Background People living with HIV (PLWH) who use tobacco face significant public health risks compared to non-users, including an average loss of 12.3 years of life expectancy. Tobacco use increases the likelihood of non-communicable diseases (NCDs), such as cardiovascular diseases, hypertension, diabetes mellitus, and non-AIDS-related cancers. Aim This study investigated factors associated with tobacco smoking and smokeless tobacco (SLT) use among PLWH in Zambia. Methods Data were obtained from a national cross-sectional survey involving 5,204 PLWH from 193 clinics across Zambia's 10 provinces. Tobacco smoking, SLT use, behavioral patterns, and clinical characteristics were assessed. Logistic regression was used to determine unadjusted (UOR) and adjusted odds ratios (AOR) at a 95% confidence interval (CI). Results Among the 5,204 PLWH surveyed, 9.7% were current tobacco smokers (21.9% men, 3.7% women), while 1.4% used smokeless tobacco (1.81% men, 1.26% women). In the multivariable analysis, several factors were identified as predictors of tobacco smoking. Male individuals had significantly higher odds of smoking (AOR: 4.81, 95% CI: 3.36-6.90). In contrast, higher educational attainment was associated with lower odds of smoking (AOR: 0.29, 95% CI: 0.16-0.52). Alcohol consumption was associated with an increased likelihood of smoking (AOR: 4.97, 95% CI: 2.93-8.44). Additionally, overweight or obese individuals were less likely to smoke, with adjusted odds ratios of 0.55 (95% CI: 0.35-0.85) and 0.36 (95% CI: 0.17-0.79), respectively. Non-adherence to antiretroviral therapy (ART) was also associated with higher smoking rates (AOR: 1.75, 95% CI: 1.14-2.67). Similarly, several factors were identified as predictors of smokeless tobacco (SLT) use. Individuals with an annual income exceeding 4,000 ZMW had lower odds of using SLT (AOR: 0.31, 95% CI: 0.14-0.73). In contrast, alcohol users exhibited significantly higher odds of SLT use (AOR: 14.74, 95% CI: 1.99-109.02). Furthermore, non-adherence to ART was associated with an increased likelihood of SLT use (AOR: 3.32, 95% CI: 1.54-7.17). Conclusions Our findings highlight the urgent need for targeted interventions to reduce tobacco use among PLWH in Zambia. Integrating these measures within the existing healthcare framework can maximize impact. Gender-specific programs addressing unique risk factors, alongside economic empowerment initiatives for low-income females, could help curb SLT use. Additionally, reinforcing ART adherence through tobacco cessation counseling within HIV care settings may lower smoking rates. Given the strong association between alcohol consumption and tobacco use, structured behavioral interventions and support programs should also be prioritized. Strengthening collaborations between health authorities and community organizations can further enhance accessibility and outreach. By embedding these strategies within primary care and ART clinics, Zambia can effectively reduce tobacco use among PLWH, ultimately improving overall health outcomes and strengthening HIV management efforts.